Organização e gestão do Centro Cirúrgico de um Hospital Universitário de Belo Horizonte - Minas Gerais - Maria do Carmo de Souza Mota Avelar Gomes (2009)
Hospitals stand out as a convergence center of several knowledge and practical health servicesystems. As a complex institution, crossed by multiple interests, hospitals suffer permanentand continuous discussion about the municipal manager, workers and users expectationrelated to its role in integral care production with quality, efficiency and costs control. In thiscontext, the HOSPITAL DAS CLÍNICAS DA UNIVERSIDADE FEDERAL DE MINASGERAIS (HC-UFMG), a public university institution, has introduced, in 1999, a newmanagement proposal based on decentralization of administrative actions, creating theFunctional Units (UF). The new management model proposes to reorganize the logical ofhospital management, in order to obtain better results and better performance in healthservices. But, in 2005, the HC-UFMG surgical center has organized itself as a Functional Unitand also has started to be responsible for management of human, financial and materialresources, processes and results, the evaluation of assistance, the teaching and the researchdeveloped in this sector. The surgical center unit is a great creator of costs to hospitals and,because of that, the development of programs which guarantee quality is a necessity in termsof efficiency and an obligation of ethical and moral point of view. In 2008 the results of aperformance evaluation has pointed inefficiency and low productivity, requiring adjustments.This study has as objective to analyze the surgical center organization and functioning, inorder to understand its management process, the factors that help and those that difficult thework process and the relationship between the different professionals who act in the unity. Ithas been done a qualitative case study, in which the data were collected through semistructuredinterviews carried out with 19 professionals, of different areas, who act in the HCUFMGsurgical center. The results were subjected to the analysis of content, using theidentification of thematic units, grouped into categories by affinity empirical. The analysis ofdata shows that the surgical center is a sector which the work is stressful, there is a great timefor the completion of surgery, interpersonal relationships and between professions areconflicting and there is predominance of medical power on the other professionals. Themanagement of the sector lacks the autonomy needed to put in place the necessary changes,due to the strength of corporate professionals, especially medical doctors. The surgical centerdid not incorporate, in its practice, the decentralized management model proposed to HCUFMG,keeping itself in a management format, parallel to the directives of the hospital,crossed by multiples powers which exist inside the service. The relationship between thedifferent professionals who act in the unity and the new management model and theorganizational changes proposed happens formatted by the corporative logic of professions.The data show that the planning, as an instrument of management, does not exist. It alsoshows that the initiative of organization and efficiency suffers interference of the medicalpower, because they requires from the directorship the same power of decision that they haveon surgical procedures, not recognizing the organizational standards. The difficulties for theorganization and operation of the surgical center are related to the shortage of managerialstrategies able to consider the various powers, seeking a team work in which the respect to thevarious workers and the hospital rules predominate. Is important also to seek integration withother sectors of the hospital as a way to organize the daily work, minimizing externalinterference.